2016
DOI: 10.1139/cjpp-2015-0070
|View full text |Cite
|
Sign up to set email alerts
|

Tranilast ameliorates cyclophosphamide-induced lung injury and nephrotoxicity

Abstract: The world-wide increase in cancer incidence imposes a corresponding significant increase in the use of chemotherapeutic agents. Nephrotoxicity is a side effect frequently encountered with cyclophosphamide (CP), which is also well-known to cause acute and chronic lung toxicities. The current study focuses on the evaluation of the potential protective efficacy of tranilast against acute and subacute CP-induced lung and kidney injuries in male Swiss Albino mice. Intraperitoneal CP significantly impaired oxidant/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…This protective effect appeared in the form of significant elevation of liver GSH and SOD with significant depletion of liver MDA compared to TAA group. These results are in agreement with (Said et al 2016) who found that tranilast administration significantly decreased MDA content in lung and kidney homogenates, suggesting decreased lipid peroxidation, generation of ROS and a positive influence on the host antioxidant defenses. Moreover, (Miyachi et al 1987) reported that tranilast significantly reduced all ROS levels and this antioxidant effect was related to its ability to scavenge ROS through direct inhibition of nicotinamide adenine dinucleotide phosphate oxidase (NADPH oxidase) and/or xanthine oxidase activity.…”
Section: Discussionsupporting
confidence: 93%
“…This protective effect appeared in the form of significant elevation of liver GSH and SOD with significant depletion of liver MDA compared to TAA group. These results are in agreement with (Said et al 2016) who found that tranilast administration significantly decreased MDA content in lung and kidney homogenates, suggesting decreased lipid peroxidation, generation of ROS and a positive influence on the host antioxidant defenses. Moreover, (Miyachi et al 1987) reported that tranilast significantly reduced all ROS levels and this antioxidant effect was related to its ability to scavenge ROS through direct inhibition of nicotinamide adenine dinucleotide phosphate oxidase (NADPH oxidase) and/or xanthine oxidase activity.…”
Section: Discussionsupporting
confidence: 93%
“…Acrolein interferes with the tissue antioxidant defense system, increases lipid peroxidation and produces ROS [37]. Various studies have consistently demonstrated that CP induces nephrotoxicity by increasing the oxidative stress specifically ROS [5,33,36,38]. These reports have suggested that overproduction of ROS impairs the kidney functions, which is accompanied by increasing in serum Cr and BUN levels.…”
Section: Discussionmentioning
confidence: 99%
“…CP decreases the activity of antioxidant enzymes, such as superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) as well as levels of non-enzymatic antioxidants [4][5][6][7]. At the same time, CP increased the lipid peroxidation product malondialdehyde (MDA) [8] and tumor necrosis factor-α (TNF-α) [9] in the lungs of mice and rats, respectively.…”
Section: Introductionmentioning
confidence: 99%